IN THE CONTEXT OF MODERNITY AND GLOBALIZATION THE RADICALIZATION ISSUE OF RELIGIOUS GROUPS IN TURKEY - Hüseyin ARSLAN (Fırat University, 2020)
Modernization and globalization are two important processes for human beings. Both processes have undergone significant changes in social life. In this sense, the most important social institutions affected by modernization and globalization are religion and religious groups that are the bearers of religion. Modernity has given great importance to the mind. Therefore, it has applied rational principles in social relations and institutions. Therefore, modernity is called “Age of Reason. In the modern era, especially with secularization, the power and influence of religion began to disappear and religion was replaced by models of explanation of rational science. Therefore, it is possible to say that modernism confines religion to a narrow space. Although modernism imprisoned religion in such a narrow space, with the onset of globalization, the obstacles to religion began to disappear. In other words, people witnessed the revival of religion in social life and the return of the sacred during the period of globalization. Religious groups in Turkey also influenced by modernity and globalization processes and have begun to come up with a variety of claims. The basis of these claims is the discourse that religious groups are secularized and distanced from their essential duties. That's the purpose of this study to discuss the religious groups in Turkey how they begin to secularization and radicalization. The first step is to focus on the role of religion in the modern and global era in the West. Then, moving from the current situation are discussed the danger of radicalization of secularized religious groups in Turkey. Finally, various proposals are made in order to prevent the radicalization of religious groups in Turkey.